Penjualan Dan Pemasaran Produk Terasi Toko Online Berbasis Website (Studi Kasus: CV. Kelapa Jaya Jontro, Kabupaten Pati) - Bahtiar, Muhammad, Moch. Djunaidi, ST, MT (2017)
Cv. Palm Jaya is a company engaged in food processing industry especially in the product processing industry home industry by advancing the quality of goods and services with good to consumers. The design used in this research is the approach on the company products Terasi till tice of the case study of CV. Coconut Jaya. In its approach method using methods that structured and integrated in the system in the sales and marketing online based on the website using the prototype method, with the tool in the form of CMS, DFD, and the designer of the proposed database into the ERD. While in the design of the system using software MySql, PHP, and Dreamwaver. The results of the study showed that the design of the system sales and online reservation based on the website easier for consumers company CV. Coconut Jaya in order and selling products namely consumers live register to order and select the appropriate product with the desire through the site already exists and then log in to enter the site already available and start to product order Terasi till tice. And implement system interface to the application that produced. The last phase of the testing process management information system based on the website using Blackbox method so that the system really can be tested with expected. Key Words: sales management information system and ordering, Website.